1994
DOI: 10.1210/endo.134.6.8194479
|View full text |Cite
|
Sign up to set email alerts
|

Two glucose-signaling pathways in S14 gene transcription in primary hepatocytes: a common role of protein phosphorylation.

Abstract: Transcription of the rat S14 gene is induced in response to increased carbohydrate metabolism in the liver. Because carbohydrate-induced changes in lipogenesis are mediated in part by changes in phosphorylation of multiple proteins, we investigated the role of protein phosphorylation on transcriptional regulation of the two carbohydrate response elements, a thyroid hormone receptor-independent carbohydrate response element and a thyroid receptor-dependent glucose response element located up-stream of the S14 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The precise identity of the accessory factor for the S14 CHORE has yet to be established. The effect of carbohydrate on S14 gene regulation involves both protein phosphorylation (51), and the maintenance of a specific intracellular calcium pool that signals for reduced transcription (52), indicating further complexity of the regulatory system.…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%
“…The precise identity of the accessory factor for the S14 CHORE has yet to be established. The effect of carbohydrate on S14 gene regulation involves both protein phosphorylation (51), and the maintenance of a specific intracellular calcium pool that signals for reduced transcription (52), indicating further complexity of the regulatory system.…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%
“…Our previous study indicated that glucose metabolites generated after the aldolase step of glycolysis were capable of stimulating expression of PPSS II mRNAs (Ehrman et al , 2000). It is conceivable that one or more of these metabolites could activate specific trans -acting factors that, in turn, modulate gene transcription via carbohydrate-responsive elements (CHORE) in promoter regions of the SS genes, as is the case for other glucose sensitive genes ( e.g ., S14; Sudo and Mariash, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that calcium ionophore A23187 was used as a CaM kinase activator, because of the ability to enhance intracellular Ca 2+ [43,44]. Lethal toxicity induced by compound 506 in mice was completely prevented by calcium ionophore A23187 administered 15 min after injection of compound 506 (Table 1).…”
Section: Discussionmentioning
confidence: 99%